Geographic concentration and spatial inequality: Two decades of EPO patenting at the level of European micro regions - Julian P. Christ (Universität Hohenheim, 2010)
This paper contributes with empirical findings to the research on structural inequality and geographic concentration of European inventorship activity at the level of European micro regions. We analyze the spatial structure and dynamics of 43 technology fields (ISI-SPRU-OST concordance) and 6 high-technology fields based on data on EPO patent applications and EPO inventors for the reference period 1977-2004. Based upon OECD RegPAT database (January 2009), we extract EPO patent applications (fractional counting) and inventor IDs (full counting), which are spatially linked to 819 European micro regions (OECD TL3), covering the EU-25, Switzerland and Norway. Besides standard descriptives, we compute Herfindahl-Hirschman indices, location quotients and weighted locational and spatial GINI coefficients. We confirm the hypotheses that (i) the technology fields under analysis differ in their overall size with respect to the stock of EPO patent applications and inventors; (ii) the share of regions with LQ > 1 has decreased compared to the share of regions with at least a single patent application; (iii) the sample of European regions is characterized by highly concentrated and unequally distributed technology fields; (iv) spatial inequality of EPO patenting and inventor location has decreased significantly within the last two decades for most technology fields. In this respect, our quantitative approach clearly depicts dispersion tendencies and decreasing inequality, although structural dynamics differ between technology fields.
urn:nbn:de:bsz:100-opus-4831
Keywords: C8; O31; O33; R12; 330; geographic concentration; RegPAT; EPO patenting; GINI coefficient; location quotient; inventorship; inequality; Erfindung; Hochtechnologiesektor; Patent; Regionale Konzentration; Regionale Disparität; Schätzung; EU-Staaten; Schweiz; Norwegen